Penerapan Sistem Informasi Kasir Berbasis Android pada MJ Autocare - Fenilinas Adi Artanto; Ahmad Khambali; Lia Khoirun Nisa; Aqika Ari Yogiana (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
This community service activity aims to improve the efficiency of financial management and operational services for UMKM, especially at MJ Autocare, a touchless motorcycle washing service business, through the development and training of an Android-based cashier application. This application is designed with three access rights for users: admin, cashier, and owner, thus simplifying transaction recording, product management, and the preparation of daily, weekly, and monthly financial reports. The implementation method includes socialization, hands-on training, and participant skill evaluation with pre- and post-tests. The training participants consisted of six MJ Autocare employees who play a direct role in operations such as cashiers and admins. The evaluation results showed a significant increase in participant understanding, where before the training only 16.7% of participants understood the basics of the cashier information system, while after the training this increased to 93.3% of participants were able to operate the application and produce financial reports independently. The main supporting factors for this activity were participant enthusiasm and the suitability of the application to partner needs, while the obstacle faced was the difference in technological understanding among participants. With this cashier application, it is hoped that MJ Autocare will be able to improve the accuracy of transaction recording, employee work efficiency, and transparency of financial reports, thereby supporting more modern and professional business management.